Analysis of complete chloroplast genome sequence of Korean landrace Cymbidium goeringii - Wang, Heng (3 Biotech, 2020)
The complete chloroplast genome sequence of Korean Cymbidium goeringii acc. smg222 was analyzed. Based on a comparison with Chinese C. goeringii, losses of nine ndh subunits (ndhA, ndhB, ndhC, ndhD, ndhE, ndhF, ndhH, ndhJ, and ndhK), three protein-coding genes (ycf 1-like, ycf 15, and ycf 68), six transfer RNAs, and one conserved open reading frame (orf 42). In addition, 219 InDels (insertion or deletion) and 171 simple sequence repeats were observed. Twenty-Five of which InDel markers have been evaluated, that useful for distinguishing Korean and Chinese Cymbidium associations based on the polymorphisms of chloroplast genomes between Korean Cymbidium goeringii acc. smg222 and Chinese C. goeringii and evaluation of genetic diversity. Finally, the phylogenetic relationships of the 39 Korean and 22 Chinese species was constructed based on the five InDel markers of them and obtained high support, indicating that our data may be useful in resolving relationships in this genus. The information about chloroplast DNA structure and gene variants of C. goeringii acc. smg222 chloroplast genome will provide sufficient phylogenetic information for resolving evolutionary relationships. The molecular markers developed in here will contribute to further research of Cymbidium species and conservation of endemic Cymbidium species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13205-019-2020-1) contains supplementary material, which is available to authorized users.